Bitcoin’s limited adoption problem - Hinzen, Franz J.; John, Kose; Saleh, Fahad (Journal of Financial Economics, 2022)
We demonstrate theoretically that Bitcoin’s limited adoption arises as an equilibrium outcome rather than as a short-lived property. Our results are driven by negative network effects which arise due to Bitcoin’s need for consensus and the existence of network delay. As the Bitcoin network expands, network delay grows thereby prolonging the time needed for generating consensus. In turn, transaction settlement becomes prolonged, and users abandon the system, yielding limited adoption. Increasing transaction rates fails to solve this problem because increasing transaction rates increases fork probabilities which prolongs the consensus process and generates limited adoption.